1969
DOI: 10.1002/zaac.19693660306
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis der neuen Phosphorsulfidphase P4S9. I. Über die Bildung von P4S9 bei der Hydrolyse von Phosphorthiochlorid im Einschlußrohr

Abstract: Bei der Hydrolyse von PSCl3 im Bombenrohr wird neben einem Polyphosphorsäuregemisch die neue Phosphorsulfidphase P4S9–x (x = 0–0,54) gebildet. Ein möglicher Reaktionsmechanismus für diese Umsetzung wird diskutiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1970
1970
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…This suggests that reactions in which P4S3 is broken down into atoms or small fragments tend to overestimate the thermodynamic stability of the caged structure. The question that naturally arises is which of the reactions (3)(4)(5)(6)(7)(8)(9) gives the best enthalpy of formation for P4S3? One way to tackle this question is to look for a reaction that predicts fairly converged ∆fHº298 values at the CCSD(T)/CBS level.…”
Section: Ccsd(t)/cbs and Ccsdt(q)/cbs Enthalpies Of Formation Of P4s3...mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that reactions in which P4S3 is broken down into atoms or small fragments tend to overestimate the thermodynamic stability of the caged structure. The question that naturally arises is which of the reactions (3)(4)(5)(6)(7)(8)(9) gives the best enthalpy of formation for P4S3? One way to tackle this question is to look for a reaction that predicts fairly converged ∆fHº298 values at the CCSD(T)/CBS level.…”
Section: Ccsd(t)/cbs and Ccsdt(q)/cbs Enthalpies Of Formation Of P4s3...mentioning
confidence: 99%
“…2,4,5,6,7 Later this collection was extended to include the notably less stable P4S5, P4S6, P4S8 and P4S9. 8,9 After this narrowing of the field, the more recent research focus in the subject area has been on the unusual cage-like structures of the phosphorus sulfides and 31 P NMR and X-ray diffraction studies have allowed for numerous structural isomers to be identified. 3,9,10,11,12,13,14,15 The majority of the known isomers of the form P4Sn can be produced in complex mixtures from the oxidation of phosphorus by sulfur at temperatures below 100° C. 16 It has been hypothesised that under such conditions an initial reactive P4S8 intermediate including a P4 cage and a cyclic S8 structure is formed.…”
Section: Introductionmentioning
confidence: 99%
“…In der Reihe der Phosphorsulfide mit Adamantangeru È st gibt es fu È nf mo È gliche Verbindungen, von denen drei bekannt sind: na È mlich P 4 S 10 [1], a-P 4 S 9 1) [2,3] und a-P 4 S 8 [4]. Von P 4 S 10 [5] und a-P 4 S 9 [6] sind Kristallstrukturen bestimmt worden, wa È hrend die Charakterisierung von a-P 4 S 8 ausschlieûlich mit Hilfe der 31 P-NMR-Spektroskopie in Lo È sung erfolgte.…”
Section: Phenylphosphineunclassified
“…The apparent cleanness of the second step of equation (1) suggests that P4S7 could result from direct extrusion of the bridge S atom in the PIII-S-PIII group of P4S8, much in the same way as organic PI11 compounds desulphurize episulphides to alkenes8 or 9-thiabicyclo[3.3.1 Inonane to cis-bicyclo[3.3.0]-~c t a n e . ~ Dilution slows down the decomposition of P4S,; hence, we suspect it to take place or start by bimolecular sulphur atom transfer between two P4S8 molecules (est.…”
Section: Nmr Evidence For the Existence Of Ps8mentioning
confidence: 99%